Stress magnification due to carbon nanotube agglomeration in composites. (1st December 2015) - Romanov, Valentin S.; Lomov, Stepan V.; Verpoest, Ignaas; Gorbatikh, Larissa
Abstract: While poor dispersion of carbon nanotubes (CNTs) is often blamed for degradation of properties of CNT reinforced polymers and their composites, the evidence that CNT agglomerates generate stress concentrations is based on common sense and, to a large extent, indirect. The present study investigates the effect of CNT agglomerates on the inter-fiber stresses in a unidirectional fiber reinforced composite using a numerical approach. The two-scale model recently developed by the authors allows simulating realistic CNT agglomeration scenarios. A parametric study is performed focusing on the size and density of CNT agglomerates as well as on the degree of agglomeration from perfectly dispersed to partially and fully agglomerated states. The study concludes that CNT agglomerates of a higher density and bigger size produce higher stress concentrations. They also give rise to higher stresses at the fiber/matrix interface. The least disturbance on the stress fields is introduced by homogeneously dispersed CNTs.